Implementasi Metode Moora Dalam Sistem Pendukung Keputusan Pemilihan Pimpinan Proyek Pada PT. PP Proyek Bendungan Lau Simeme - Natalius Tafonao; Guidio leonarde Ginting; Ryan Syahputra (KOMIK (Konferensi Nasional Teknologi Informasi dan Komputer), 2022)
The selection of project leaders must be done by determining several main criteria to consider in determining the quality of each company. One of the problems that are often faced in selecting project leaders at PT. The PPs for the Lau Simeme Dam Project are many of the prospective project leaders who meet the criteria. This causes the election organizers to be confused in determining the right project leader. One way that must be done to help the PT. PP Lau Simeme Dam Project in the decision-making process to determine the project leader is the need for a computer-based application in the form of a decision support system that can provide solutions to decision making. Decision Support System (DSS) is a system used by management in producing a decision from an existing problem. The Multi-Objective Optimization On The Basic of Ratio Analysis (MOORA) method is one method that can make a decision based on the concept of ranking by comparing the index value of each alternative to the overall index value of the alternative. In the process of selecting project leaders at PT. PP Lau Simeme Dam Project uses the Multi-Objective Optimization On The Basic of Ratio Analysis (MOORA) method, resulting in the highest weight value that will be taken into consideration in selecting the project leader. The results obtained in this process determined that alternative A1 on behalf of Yudi Priyanto has a high ranking value with a score of "25.6".